2011
DOI: 10.1063/1.3518981
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-graphite interaction: Experimental evidences of an adsorption barrier

Abstract: The interaction of H atoms having relatively low average kinetic energy (∼0.025 eV) with both perfectly clean and D-covered HOPG surfaces is investigated using high resolution electron energy loss spectroscopy. From this study we confirm, in a controlled fashion, the presence of the theoretically predicted adsorption barrier since no adsorption is detected for such H atoms on HOPG. Moreover, we demonstrate that the exposure of a D saturated HOPG surface to these H atoms results in the complete removal of adato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 37 publications
7
32
0
Order By: Relevance
“…Despite this, para DF shows a dynamical threshold of about 2 kJ·mol −1 (corresponding to a gas-phase temperature T g ∼ 300 K), below which only H 2 recombination is expected. This is in agreement with recent experiments, in which highly oriented pyrolitic graphite (HOPG) samples precovered with D atoms were found to form dimers and clusters only when irradiated with highly energetic H atoms (23); at E coll = 2.4 kJ·mol −1 , only ER recombination was found to occur (24). More generally, as is evident in Fig.…”
Section: Resultssupporting
confidence: 80%
“…Despite this, para DF shows a dynamical threshold of about 2 kJ·mol −1 (corresponding to a gas-phase temperature T g ∼ 300 K), below which only H 2 recombination is expected. This is in agreement with recent experiments, in which highly oriented pyrolitic graphite (HOPG) samples precovered with D atoms were found to form dimers and clusters only when irradiated with highly energetic H atoms (23); at E coll = 2.4 kJ·mol −1 , only ER recombination was found to occur (24). More generally, as is evident in Fig.…”
Section: Resultssupporting
confidence: 80%
“…It has now been well established that sticking is an activated process, with a barrier related to the surface reconstruction accompanying the sp 2 → sp 3 re-hybridization of the carbon atom involved in the bond formation process. 3 As a consequence, carefully conducted scattering experiments which used low energy hydrogen atom beams -as opposed to high energy beams obtained by thermal cracking of H 2 -found that the competing, non-activated hydrogen abstraction process dominates under these conditions, 19 a result which was later confirmed by ab initio molecular dynamics simulations. 25 For all but the smallest coverage, hydrogenation is driven by electronic and substrate-softening effects which lead to dimer formation and clustering; 15,18,26,27 hence, current experimental results leave the question open of how large is the initial hydrogen sticking coefficient on the carbon sheet.…”
Section: Introductionmentioning
confidence: 82%
“…Though experimental studies have shown adsorption-induced metal-insulator transitions, 7,8 reversible opening of a band-gap 9,10 and even ferromagnetic hysteresis, 11 the necessary precise control on the hydrogenation process has yet to be achieved. Hydrogenation of graphite has been studied in a number of experimental works, 3,[12][13][14][15][16][17][18][19][20][21][22][23][24] with a variety of surface-science techniques including thermal desorption, high-resolution electron-energy-loss spectroscopy, scanning tunneling microscopy, low-energy electron diffraction, angle a) Electronic mail: matteo.bonfanti@unimi.it b) Electronic mail: rocco.martinazzo@unimi.it resolved photo-emission spectroscopy, and X-ray photoemission spectroscopy. It has now been well established that sticking is an activated process, with a barrier related to the surface reconstruction accompanying the sp 2 → sp 3 re-hybridization of the carbon atom involved in the bond formation process.…”
Section: Introductionmentioning
confidence: 99%
“…The most well-defined experiment performed to date placed the barrier for H atom adsorption on graphite somewhere within the rather broad range of 25 to 250 meV. 31 Previous theoretical work on extended carbonaceous surfaces (graphite, and more commonly a single graphene layer) have been at the upper end of the experimental range (ca. 200 meV 16,19,[32][33][34][35] ).…”
mentioning
confidence: 99%